Efeito das técnicas de polimento e tempo na rugosidade superficial, dureza e microinfiltração de restaurações de resina composta após um ano de armazenagem - Venturini, Daniela (2006)
This study evaluated the effects of immediate and delayed polishing on surface roughness (Ra), microhardness (KHN) and microleakage of a microfilled composite (Filtek A110) and a hybrid composite (Filtek Z250) restorations after one-year storage. Standardized cavities preparations were made in the buccal surface of 256 bovine teeth; half were restored with each composite. Immediately after photo activation finishing was carried out with #280 grit sandpaper. For each composite, the specimens were randomly allocated for two sub-groups. The first group (IM) was immediately polished, using three different systems (n=16): A- Sof-Lex; B- Flexicups; and C- a sequential technique using Flexicups, Jiffy Polishing Brush and Flexibuffs. The specimens were stored in saline solution at 37ºC. The second group (DE) was stored for two weeks and then polished with the same systems. Part of the specimens had their surface properties analyzed at the baseline, and the remaining specimens were stored for one-year in distilled water at 37ºC. Five readings per specimen were taken for each specimen regarding surface roughness and microhardness. After immersion in basic fuchsin, microleakage was evaluated (X40) using standardized scores. Data were analyzed at significance level of 0.05 with analysis of variance and a SNK test (surface roughness and microhardness) or with Mann-Whitney and Kruskal-Wallis (microleakage). For comparison between baseline and one-year Student´s t test (Ra) and Mann-Withney (microleakage) were carried out. After one-year, in general microfilled composite specimens showed lower roughness and hardness. No difference regarding microleakage was observed among different groups, but better sealing was observed in enamel margins. The sequential technique provided the lowest roughness and the Sof-Lex the lowest hardness in the most of the experimental conditions. Aging increased composite roughness. Immediate polishing showed similar or better performance than delayed polishing for microleakage and surface roughness, but this was not observed for microhardness, except in sequential technique groups